Social and contextual factors associated with drinking before, during and after watching Australian Football League games: A pilot ecological momentary assessment study - Pennay, A.; van Egmond, K.; Anderson-Luxford, D.; Wright, C.J.C.; Caluzzi, G.; Livingston, Michael; Dickson, G.; Nicholson, M.; Kuntsche, E. (2023)
Introduction: The aim of this study was to: (i) determine the feasibility of using ecological momentary assessment to collect data from Australian Football League (AFL) fans; (ii) explore pre-game, during-game and post-game consumption patterns of AFL fans; and (iii) explore the social and setting-related factors associated with risky single occasion drinking (5+ drinks) among AFL fans. Methods: Thirty-four participants completed up to 10 ecological momentary assessment surveys before, during and after 63 AFL games (n = 437 completed surveys). Surveys collected data about their drinking, and their social and environmental milieu (e.g., location, company). Binary logistic regression analyses clustered by participant identified which game-day characteristics were associated with higher odds of risky single occasion drinking. Significant differences between pre-game, during-game and post-game drinking on social and environmental factors were explored using pairwise comparisons. Results: Risky single occasion drinking was more likely when games began in the early-afternoon (1–3 pm) than late-afternoon (3–6 pm), when participants watched the game at a stadium or pub compared to home, and when participants watched the game with friends compared to family. Pre-drinking was more likely before night games and post-drinking was more likely after day games. Drinking during the game was heavier when watching the game at a pub and when watching with a combined group of friends and family. Discussion and Conclusions: Preliminary findings suggest that social and contextual factors matter in the way alcohol is consumed while watching AFL games. These findings require further investigation in larger samples.